Illegal selective logging and forest fires in the northern Brazilian Amazon - Condé, Tiago Monteiro (Forests, 2020)
Illegal selective logging and forest fires occur on a large scale in the northern Brazilian Amazon, contributing to an increase in tree mortality and a reduction in forest carbon stock. A total of 120 plots of 0.25 ha (30 ha) were installed in transitional ecosystems or ecotones (LOt) between the forested shade-loving campinarana (Ld) and dense-canopy rainforest, submontane (Ds), in the National Forest (Flona) of Anauá, southern Roraima. Measuring the diameters at breast height (DBH ≥ 10 cm) and the heights of 171 dead trees (fallen naturally, illegally exploited, and affected by forest fires), enabled the estimation of carbon content from the application of a biomass equation developed at Manaus, and the calculation of a correction factor, using the average height of the largest trees. From 2015-2017, we mapped the real extent of illegal selective logging and forest fires across the region with CLASlite and INPE/Queimadas. From measurements of 14,730 live and dead trees across 30 hectares (491 ± 15 trees·ha -1 ), the illegal selective logging and associated forest fires, and aggravation by severe El Niño droughts resulted in an 8.2% mortality of trees (40 ± 9 dead trees·ha -1 ) and a 3.5% reduction in forest carbon stock (6 ± 3 Mg·ha -1 ) in the short-term. The surface area or influence of forest fires of very high density were estimated in the south-central region of Roraima (8374 km 2 ) and the eastern region of the Flona Anauá (37 km 2 ). Illegal selective logging and forest fires in forest areas totaled 357 km 2 in the mosaic area, and 6 km 2 within Flona Anaua. Illegal selective logging and forest fires in the years of severe El Niño droughts threatened the maintenance of environmental services provided by Amazonian forests. © 2019 by the authors.